High resolution 3D subsurface mapping using a towed transient electromagnetic system ‐ tTEM: case studies. Issue 3 (13th March 2020) - Maurya, Pradip Kumar; Christiansen, Anders Vest; Pedersen, Jesper; Auken, Esben
ABSTRACT: Geophysical methods are routinely applied for investigation of near surface in areas of infrastructure, water supply, artificial infiltration, farming, waste deposits, construction, etc. A new towed transient electromagnetic tool, called 'tTEM', provides rapid, efficient, high‐resolution imaging of subsurface hydrogeology, and can deliver densely spaced profiles of resistivity. These profiles can be used to map a three‐dimensional subsurface in high resolution. In this paper, we present three case studies where the towed transient electromagnetic system was used to map the subsurface at the hectare scale. In the first case, we used towed transient electromagnetic to map raw materials in the northern Jutland, Denmark. The survey was carried out to map possible sand and gravel deposits. In the towed transient electromagnetic models, the potential sand/gravel targets are identified as high resistive bodies in the top 30 m. These bodies can have significant lateral variation at scales much less than one hundred metres. In the second case study, towed transient electromagnetic was used to map the thickness of a protecting clay layer above an aquifer in Vildbjerg, a town in the central part of Denmark. Results show that the overlying clay layer has sufficient thickness (>15 m) to protect the underlying aquifer from pesticide pollution in the area. Finally, in the third case study, we used towed transient electromagnetic for mapping geology in the vicinity of a landfill. The inversion results reveal a hitherto unknown buried valley‐like feature within the top 30 m of the subsurface that was not identified by older, regional TEM surveys – a feature that can have significant impact on the water flow.